Effect of processing conditions on the bioactive compounds and biological properties of bee pollen - Dias, L.G. (2018)
Bee pollen has had a valued place in traditional medicine for centuries, even though its use in modern medicine is still limited by the lack of scientific evidence. In this study, we characterized and compared nine types of bee pollen, submitted to two preservation methods (lyophilization and drying), in relation to the content of phenolic compound and total flavonoids. The biological properties were also evaluated and compared. Pollen analysis allowed us to classify two samples as heterofloral, whilst the remaining were monofloral. The concentrations of flavonoid and phenolic compounds were greater in the lyophilized samples. Even though all samples presented antimicrobial activity, the lyophilized ones induced stronger inhibition against both Gram-negative and Gram-positive bacteria. For the yeasts studied, the difference between the two preservation procedures was not so relevant. The antioxidant activity was also greater in the lyophilized samples. Antimutagenic capacity was observed in all samples, independently of the preservation method, even though some bee pollen types decreased the number of gene conversion and mutant colonies more efficiently. In conclusion, the results suggest that lyophilization is better to preserve the bioactive compounds and biological properties of this natural product.